ESRA19-0108 Cost-effectiveness analysis after the implementation of an eras protocol in elective colorectal surgery. (30th August 2019) - Cabellos, M; Muñoz, R; Labalde, M; Torralba, M; Rodriguez, JR; Atance, JC
Abstract : Background and aims: The aim is to evaluate the effectiveness of an ERAS program based on hospital length of stay (LOS), readmission rates and postoperative complications, and to know if it was cost-effective. Methods: We compared 121 consecutive patients (ERAS group) operated on elective colorectal surgery according to an ERAS protocol, with a historical cohort of 135 (preERAS group) operated before the protocol. Inclusion criteria: elective colorectal surgery, ≥18 years, appropriate cognitive state and ASA I-II-III. Exclusion criteria: urgent surgery and higher concomitant surgical processes. The results are presented as number of patients and percentage (%) (preERAS vs ERAS) or mean ± standard deviation. Results were statistically significant when p<0.05. Results: Two groups were homogeneous, except there was more laparoscopic surgery in the ERAS group (27 [20%] vs 45 [37.2%], p = 0.006). The mean compliance of the protocol was 72.5% ± 11.40%. In the ERAS group, a decrease in LOS was observed (11 ± 3.8 vs 9.8 ± 3.7, p = 0.018), without increasing the complication rate (49 [36.3%] vs 38 [31.4%], p = 0.49), readmissions at 30 days after hospital discharge (15 [11.1%] vs 12 [9.9%], p = 0.756), mortality at 30 days after hospital discharge (1 [0.7%] vs 2 [1.7%], p = 0.498) and healthcare costs (average cost per patient) (1618.8€ ± 830.5 vs 1578.6€ ± 491.1, p = 0.634). Conclusions: ERAS protocol in elective colorectal surgery is cost-effective, because it improves the results (reduces LOS without increasing the rate of complications or readmissions) without increasing healthcare costs.